Feasibility of a peer mentoring programme for young adults with intellectual and developmental disabilities and co‐occurring mental health conditions. (31st May 2021) - Schwartz, Ariel E.; Levin, Melissa
Abstract : Accessible Summary: Many young adults with intellectual and developmental disabilities also have mental health challenges, such as anxiety, depression or post‐traumatic stress disorder. Peer mentoring is when people with disabilities support another person with a disability. We worked together to make a peer mentoring programme to help young adults with intellectual and developmental disabilities have better mental health. People enjoyed peer mentoring—they thought it was fun and that their mentors were nice. A few people thought that mentoring would be better if there was more time to do activities with their mentor. Some people felt like mentoring helped them learn ways to cope with their mental health challenges. This article describes the peer mentoring programme, what people liked, what they did not like and how we want to change peer mentoring in the future. This is important, because other people might want to try peer mentoring so people with disabilities can learn from each other. Abstract: Background: We conducted feasibility testing of a novel peer mentoring intervention addressing self‐awareness and proactive coping for young adults with intellectual and developmental disabilities and co‐occurring mental health conditions. Aligned with regulatory flexibility theory, we hypothesised that if young adults with intellectual and developmental disabilities and co‐occurring mental health conditions learned a range of coping strategies, then they would have greater self‐efficacy for managing their emotions and, subsequently, decreased mental health symptoms. Methods: Five participants ( M age : 20, range: 16–22) were mentored by another young adult with intellectual and developmental disabilities and co‐occurring mental health conditions for 10 sessions. Feasibility data collected included the following: enrollment data, attendance rates, participant and parent member experiences and observation of change (via post‐intervention interviews), and mentoring satisfaction via a mentoring questionnaire (range 15–60). Findings: Our enrolment rate was 16%. Mentoring was acceptable to young adults, as demonstrated by high attendance rates (98% of sessions attended), mentoring questionnaire responses ( M =49.4) and feedback describing the intervention as enjoyable and mentors as "nice, " and "understanding." Participants and parents reported potential change in self‐efficacy for managing emotions (proximal outcome), use of coping strategies and self‐awareness of needs, but few changes in mental health symptoms (distal outcomes). Conclusions: The peer mentoring intervention was feasible and acceptable for young adults with intellectual and developmental disabilities and co‐occurring mental health conditions. Results suggest a longer intervention duration may be necessary to elicit changes in mental health symptoms. To enhance feasibility, different recruitment strategies should be considered.